The Function of Endothelin-1 (ET-1) as a Biomarker for the Early Identification of Endothelial Dysfunction in National Health Security (NHS) and Sustainable Development Goals (SDGs): A Shift in Paradigm - Pratama, Aldian (PT. Civil Military Center, 2025)
Endothelin-1 (ET-1) is a potent vasoconstrictor and functions as a non-invasive biomarker for endothelial dysfunction from a biomolecular standpoint. Endothelial dysfunction is a precursor to hypertension and various cardiovascular diseases. According to the Sustainable Development Goals (SDGs), the financial burden associated with cardiovascular diseases has been increasing annually. This necessitates a paradigm shift within the national health resilience framework, moving from a focus on illness to one that emphasizes health promotion and prevention, with the aim of mitigating the financial impact of cardiovascular diseases. The purpose of this research is to investigate the essential role of endothelin-1 (ET-1) in advancing the Sustainable Development Goals (SDGs) and enhancing national health resilience. The investigation seeks to emphasize the unique and clinical significance of endothelin-1 (ET-1) across various sectors, particularly concerning cardiovascular risk, as well as the potential economic advantages of alleviating the disease burden. The results reveal that endothelin-1 (ET-1) plays a significant role in contributing to the SDGs by facilitating the early detection of endothelial dysfunction, thereby helping to reduce the incidence of cardiovascular diseases. Originality and value lie in its use of a novel statistical analysis to explore the relationship between endothelin-1 (ET-1) and other pertinent parameters. This research highlights the integrative function of Endothelin-1 (ET-1) in harmonizing the objectives of the SDGs with those of National Health Resilience, providing actionable insights for decision-makers across various sectors. The findings establish a basis for policymakers and practitioners to utilize endothelin-1 (ET-1) in promoting comprehensive and sustainable development.